Motivation to lead in Japan: validation of a Japanese version of the motivation to lead scale - Tanaka, Satoshi; Hatano, Kai; Ikeda, Megumi; Nakahara, Jun (Frontiers in Psychology, 2024)
Introduction: This study aimed to develop a Japanese version of the Motivation to Lead (MTL) scale consisting of three factors⎯affective-identity MTL, non-calculative MTL, and socialnormative MTL⎯and examine its construct validity and reliability. Methods: The participants comprised 500 university students and 500 employees aged 20-29 years registered with a Japanese research company. Results: Based on a confirmatory factor analysis, the three-factor model was found to be appropriate for the Japanese context. The measurement invariance analyses indicated scalar invariance between students and employees and between men and women. Finally, the correlation analysis with the Big Five personality traits conducted to examine construct validity indicated that affective-identity MTL and social-normative MTL had significant relationships with all five traits (extraversion, agreeableness, conscientiousness, open-mindedness, and negative emotionality). Although non-calculative MTL was not significantly correlated, it can be interpreted in the Japanese context. Discussion: The results indicate the adequate construct validity and reliability of the Japanese version of the MTL scale. These findings hold significant implications for leadership development and selection in Japan, highlighting the motivational factors that drive effective leadership.